Efficacy and safety of drug-eluting balloon-only strategy (DEB-only) for de novo coronary artery disease: a systematic review and meta-analysis. (25th November 2020) - Zhang, W.Y; Zhang, M.D; Tian, J.F; Zhang, M; Zhou, Y; Song, X.T
Abstract: Background: Many clinical trials have demonstrated the value of drug-eluting balloon (DEB) for in-stent restenosis. Recently, DEB for de novo lesions has also attracted more attention. There have been promising results of PCI using DEB alone in selected de novo coronary diseases (small vessels, bifurcating lesions, acute myocardial infarction). However, the application of DEB for patients with de novo coronary artery disease remains controversial due to relatively limited evidence. Purpose: The purpose of this study was to evaluate the efficacy and safety DEB-only strategy (bail-out stents were allowed when required) compared with other modalities for the treatment of de novo coronary lesions. Methods: We searched PubMed, Embase, Web of Science and Cochrane Library Central Register of Controlled Trials (CENTRAL) electronic databases for randomized controlled trials as well as observational studies published up to Jan 22, 2020. Studies which compared DEB-only approach with other PCI strategies for treatment of any type of de novo coronary lesions were identified. The primary outcome was late lumen loss (LLL) during angiographic follow up. The secondary outcomes were major adverse cardiac events (MACE), target lesion revascularisation (TLR) and binary in-segment restenosis. Results: Nineteen studies (eleven randomised controlled trials and eight observational studies) with a total of 3, 356 patients were included in this meta-analysis. Angiographic observations were obtained at 6 or 9 months and clinical follow-up duration ranged from 6 months to 36 months. Among the overall studies, the results indicated that DEB-only strategy was superior to the control groups for LLL (mean difference (MD) = −0.30mm; 95% confidence interval (CI), −0.41 to −0.19; P<0.001). DEBs were associated with a similar risk of MACE (risk ratio (RR): 0.84, 95% CI: 0.64, 1.11, P=0.22), TLR (RR: 0.79, 95% CI: 0.53, 1.16, P=0.23) and binary restenosis (RR: 0.68, 95% CI: 0.35, 1.31, P=0.25) compared with the control groups. In subgroup analysis, DEB-only strategy showed significantly better outcomes for most endpoints compared to POBA. Compared with DES, there were also significant favorable effects associated with treatment of DEB-only on LLL (MD: −0.14, 95% CI: −0.23, −0.04, P=0.005), while insignificant inter-strategy differences were observed in other endpoints. Vessel diameter did not have a significant influence on the result. Conclusion: DEB-only intervention is an effective treatment associated with a significant reduction in late loss late lumen loss compared to other options. The efficacy and safety of DEB alone are comparable to those of DES and superior to POBA for treatment of selected de novo coronary lesions. Additional evidence is still warranted to confirm value of DEB before a widespread clinical utilization can be recommended. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Beijing Lab for Cardiovascular Precision Medicine